KINETICS OF MODULATORY ROLE OF Cyperus esculentus L. ON THE SPECIFIC ACTIVITY OF KEY CARBOHYDRATE METABOLIZING ENZYMES - Sabiu, Saheed; Ajani, Emmanuel Oladipo; Sunmonu, Taofik Olatunde; Ashafa, Anofi Omotayo Tom (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The continuous search for new lead compounds as viable inhibitors of specific enzymes linked to carbohydrate metabolism has intensified. Cyperus esculentus L. is one of the therapeutically implicated botanicals against several degenerative diseases including diabetes mellitus. Materials and Methods: This study evaluated the antioxidant and mechanism(s) of inhibitory potential of aqueous extract of C. esculentus on α-amylase and α-glucosidase in vitro. The extract was investigated for its radical scavenging and hypoglycaemic potentials using standard experimental procedures. Lineweaver-Burke plot was used to predict the manner in which the enzymes were inhibited. Results: The data obtained revealed that the extract moderately and potently inhibited the specific activities of α-amylase and α-glucosidase, respectively. The inhibition was concentration-related with respective IC50 values of 5.19 and 0.78 mg/mL relative to that of the control (3.72 and 3.55 mg/mL). The extract also significantly scavenged free radicals and the effects elicited could be ascribed to its phytoconstituents. Conclusion: The respective competitive and non-competitive mode of action of the extract is due to its inhibitory potentials on the activities of α-amylase and α-glucosidase. Going forward, in addition to completely characterize the exact compound(s) responsible for the elicited activity in this study, pertinent attention will be given to the in vivo evaluation of the identified constituents.